Development of Exporting Fresh Fruits Ontology for Improving the Knowledge-Based System on the Domain of Export Process in Thailand - Tangarommun, Thanisorn; Kumyaito, Nattapon; Ponanan, Klairung (ECTI Transactions on Computer and Information Technology (ECTI-CIT), 2024)
Thailand’s exports are crucial to the country’s economic income, with agricultural products among the most important. Import-export firms mainly manage the export process because agriculturists hesitate to deal with complex procedures. Based on the complex procedures and lack of knowledge about the export process, new entrepreneurs and agriculturists often struggle to export their products directly. Therefore, a simplied system is needed for those seeking information on export procedures. To address this, the Exporting Fresh Fruits Ontology was developed to en- hance the knowledge-based system for managing fresh fruit exports. This system involves three main steps: reviewing export processes and documents, generating ontology for the fresh fruit export domain, and developing the knowledge-based system. The Hozo Ontology Editor is the system’s backbone, built using the Ontology-based Application Management (OAM) framework. The Exporting Fresh Fruits Ontology comprises 12 main classes, sub-classes, and attributes, capturing knowledge of the export process. It includes mappings between relational database entities and the ontology, capturing semantic information, and validating mapping consistency to eliminate errors. The results show that the Exporting Fresh Fruits Ontology performs well, achieving an average F-measure value of 0.98.